Determinants of costs of human papillomavirus vaccine delivery in six low- and middle-income countries - Mvundura, Mercy; Slavkovsky, Rose; Debellut, Frédéric; Naddumba, Teddy; Pecenka, Clint; Scott Lamontagne, D. (Elsevier Ltd, 2024)
Evidence on determinants of vaccine delivery costs can inform program design and planning. Given the dearth of this evidence for human papillomavirus (HPV) vaccine, we conducted an analysis to identify programmatic and operational factors that are statistically associated with variations in economic costs for HPV vaccine delivery, within and across six low- and middle-income countries. HPV vaccine program operations and cost data were collected from Ethiopia, Guyana, Rwanda, Senegal, Sri Lanka, and Uganda. An ordinary least square regression analysis was done using data from 279 health facilities in these six countries. We ran country-specific and pooled multivariate linear regressions. A conditional regression including 228 facilities was also run. The dependent variable was the estimated total economic costs for HPV vaccine delivery per facility, excluding vaccine procurement costs. Explanatory variables included number of HPV vaccine doses delivered; numbers of vaccination sessions conducted, and schools served; distance traveled by health workers for vaccine delivery; intensity of conducting program activities; human resource (health workers, school staff, etc.) utilization rates; and categorical variables indicating whether per diems were paid, and for country-specific dummies; Explanatory variables such as the number of program activities or meetings held, receipt of per diems, and utilization rates of health workers, were all positively and statistically significantly associated with economic costs in the pooled sample, for both the unconditional and conditional regressions. Variables such as the doses delivered, and number of sessions conducted were statistically significant in the unconditional regression. The within-country regression found that only variations in utilization rates of health workers were statistically significant in all countries. Our analysis provides evidence to HPV vaccination program stakeholders on which program context variables impact costs, which can inform program adjustment to improve cost efficiency, especially as programs managers work to revitalize and rebuild HPV vaccine coverage after the COVID-19 pandemic.Evidence on determinants of vaccine delivery costs can inform program design and planning. Given the dearth of this evidence for human papillomavirus (HPV) vaccine, we conducted an analysis to identify programmatic and operational factors that are statistically associated with variations in economic costs for HPV vaccine delivery, within and across six low- and middle-income countries. HPV vaccine program operations and cost data were collected from Ethiopia, Guyana, Rwanda, Senegal, Sri Lanka, and Uganda. An ordinary least square regression analysis was done using data from 279 health facilities in these six countries. We ran country-specific and pooled multivariate linear regressions. A conditional regression including 228 facilities was also run. The dependent variable was the estimated total economic costs for HPV vaccine delivery per facility, excluding vaccine procurement costs. Explanatory variables included number of HPV vaccine doses delivered; numbers of vaccination sessions conducted, and schools served; distance traveled by health workers for vaccine delivery; intensity of conducting program activities; human resource (health workers, school staff, etc.) utilization rates; and categorical variables indicating whether per diems were paid, and for country-specific dummies; Explanatory variables such as the number of program activities or meetings held, receipt of per diems, and utilization rates of health workers, were all positively and statistically significantly associated with economic costs in the pooled sample, for both the unconditional and conditional regressions. Variables such as the doses delivered, and number of sessions conducted were statistically significant in the unconditional regression. The within-country regression found that only variations in utilization rates of health workers were statistically significant in all countries. Our analysis provides evidence to HPV vaccination program stakeholders on which program context variables impact costs, which can inform program adjustment to improve cost efficiency, especially as programs managers work to revitalize and rebuild HPV vaccine coverage after the COVID-19 pandemic. MEDLINE - Academic